Polycythemia Vera initially presenting with Acute Ischemic Stroke: A Case Report (Journal of Dhaka National Medical College & Hospital, 2018)
Polycythaemia Vera (PV) is an uncommon recognized cause of ischemic stroke. In the majority of cases of PV, thrombosis in cerebral artery is the main reason for ischemic stroke and if not treated, there is chance of recurrent stroke. Here, we present a case of PV who presented with acute ischemic stroke. Investigation revealed Hb% 19.4 gm/dl, hypercellular marrow without any evidence of malignancy in bone marrow and positive JAK2 mutation. We treated this case by hemodilution with venesection and later by cytoreductive drugs. The patient responded well. Early and effective treatment of PV can prevent the recurrence of stroke and other thromboembolic complications as well as increases the chance of survival.J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 48-51